Diagnostic and therapeutic value of appendoscope-assisted endoscopic retrograde appendicitis therapy - Liu, Pengcheng; Wu, Liqiong; Li, Pengju; Li, Yu; Sun, Dianzuo (Endoscopy International Open, 2025)
The appendoscope, derived from the peroral digital single-operator cholangioscope, is an endoscopic device enabling direct visualization of the appendix lumen for diagnostic or therapeutic purposes. This study aimed to investigate diagnostic and therapeutic efficacy of appendoscope-assisted endoscopic retrograde appendicitis therapy (ERAT) in patients with appendicitis.A total of 131 patients were enrolled in the study, with 125 included in the final analysis. Patient demographics, procedure success, abdominal pain resolution, appendoscope manifestations, treatment strategies, procedure time, duration of antibiotic use, postoperative hospital stay, and comorbidities were recorded. Complications and recurrences were followed up. These variables were subsequently analyzed to evaluate efficacy of appendoscope-assisted ERAT.The technical success rate of appendoscope-assisted ERAT was 98.5%, and the clinical success rate was 100%. Appendoscope visual manifestations included appendicolith (76.8%, n = 96), stenosis (16.8%, n = 21), foreign body (6.4%, n = 8), mucosal inflammation (13.6%, n = 17), and perforation (3.2%, n = 4), with these findings occurring individually or in combination. Abdominal pain disappeared within 12 hours post-procedure in 79% of patients (n = 99). Average procedure time was 50.3 ± 18.9 minutes. Antibiotic therapy duration was less than 2 days in 39% of patients (n = 49), whereas 19% (n = 24) received no antibiotics. Average postoperative hospital stay was 1.9 ± 1.4 days. Concomitant intestinal lesions were identified in 16 patients (12.8%). Recurrence occurred in 4.8% of patients (n = 6) during a 4- to 16-month follow-up. No complications were recorded.Appendoscope-assisted ERAT is a feasible, accurate, safe, and effective alternative for diagnosis and treatment of appendicitis.
Keywords: Endoscopy Lower GI Tract; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE...); Endoscopy Upper GI Tract; Dilation, injection, stenting; GI surgery